2016
DOI: 10.9734/ajaees/2016/10077
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic Variables and Food Security Status of Cocoa Farming Households in Ondo State, Nigeria

Abstract: The study investigated the effects of socio-economic characteristics on food security status of cocoa farming households. The study was conducted in Ondo State, Nigeria. There was random selection of four notable cocoa producing Local Government Areas (LGAs) and from each of the four selectedLGAs, there was random selection of two communities. However, from the eight communities, a total of two hundred respondent households were randomly selected. The data collected were analysed with descriptive statistics as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 6 publications
6
17
1
Order By: Relevance
“…28 However, that study used the 6-item HFIAS survey tool. The level of food security was much lower than levels reported from other studies in Ondo, Nigeria and Nairobi, Kenya, 29,30 but higher than what has been found in Latin America among urban households. 31 Food security was positively associated with women having higher educational levels, higher monthly household incomes, smaller household sizes and proportions of monthly income spent on food being less than 40%.…”
Section: Discussioncontrasting
confidence: 73%
“…28 However, that study used the 6-item HFIAS survey tool. The level of food security was much lower than levels reported from other studies in Ondo, Nigeria and Nairobi, Kenya, 29,30 but higher than what has been found in Latin America among urban households. 31 Food security was positively associated with women having higher educational levels, higher monthly household incomes, smaller household sizes and proportions of monthly income spent on food being less than 40%.…”
Section: Discussioncontrasting
confidence: 73%
“…To identify the dimensions of empowerment that influence women's household food security status, the Ordered Logit model was used. Various models have been used in developing countries for determining factors influencing food security status of households, such as, Tobit model (Etim and Solomon, ), Probit model (Oluyole et al., ) and Logit (Babatunde et al., ). The selection of the Ordered Logit model in this study is in line with Greene (), since the dependent variable (the household food security status) is both categorical and ordinal.…”
Section: Research Methodsologymentioning
confidence: 99%
“…Moreover, the problem of food insecurity is far more pronounced among rural households. Over 70% of rural households in south-western Nigeria are food insecure (Babatunde et al, 2007;Oxfam, 2012;Adeniyi and Ojo, 2013;Oluyole and Taiwo, 2016). Several factors such as age, household size, or lack of credit access expose rural households to food insecurity.…”
Section: Introductionmentioning
confidence: 99%